Steel Frame Construction Technology in Ottoman Architecture and Metro Khan - Yergun, Uzay; Celebioglu, Banu (TRANS TECH PUBLICATIONS LTD, 2010)
From the first quarter of the 18th century, an expansion to European civilization was beginning in Ottoman Empire and with Tanzimat period, this westernization fact had transformed to a fundamental innovation act in the structure of the state and society. European capital image gained by Istanbul created a symbolic view of change. However, a contradiction of traditional urban tissue, consisted by the timber buildings, necessitated a fundamental change in the urban and architectural structure. According to this aim, new building types which were necessary for the Tanzimat reforms (a period of time of political reforms during the Ottoman sultanate of Abdulmecid (r.1839-61) began to be constructed by the European architectural design models, with modern building materials and production technologies. In this context, construction technologies like jack arches, steel framework, fer-concrete and reinforced concrete, which are formed with structural materials like modern brick, iron beam, and concrete, are the factors of formation of the historical development process of the Ottoman architecture after the first years of the 19th century. From the middle of 19th century, use of the steel beam was beginning in the building product technology, depending on the evolution of the industrial metal technology in European countries. Technological level of the steel construction after Jack Arch, which is formed with the iron beam, has brought new expansions to the building production. As from the first years of the 20th century, buildings constructed by steel construction technology began to take place in Ottoman architecture. In this paper, the place of the steel-framed building technology in Ottoman architecture, especially the steel frame construction in the Tanzimat period buildings and their architectural design criteria will be presented. Besides, the conclusions based on the comparisons of structural and architectural design with the European architecture buildings will be indicated. Metro Khan, dated 1914, is the first building that was erected with this construction technology. This building is constructed as an administration and station building of the under ground train, named Tuner, which connects Pera and Istanbul Seaport. This paper traces the importance of the building in terms of conservation and cultural values, while benefiting from its characteristic architecture and static projects.
Keywords: Istanbul; steel-framed; station building; Eugene Henry Gavand; Construction & Building Technology; Engineering; Materials Science